Rosuvastatin Improved LDL Subfractions Profile in a Patient with Type 1 Diabetes Following a Ketogenic Diet: A Case Report - Janić, Miodrag; Lunder, Mojca; Janež, Andrej; Šabović, Mišo; Maggio, Viviana; Rizzo, Manfredi (Current Vascular Pharmacology, 2025)
<span class=
Keywords: Type 1 diabetes